Kendala Dalam Membangun Pemahaman Literasi Media Televisi dan Cara Mengatasinya (Studi Kasus di Kota Kupang) - Mas'Amah Mas'Amah; Siti Karlinah; Dadang Rahmat Hidayat; Ninis Agustini Damayani (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2020)
This research was motivated by the habit of Kupang middle school adolescents in watching television without the ability in media literacy. This research aimed to discover the problems faced in establishing the adolescents’ understanding of television literacy and the ways forward to overcome the issues. This research used a qualitative approach with a case study as a method. The results found five primary obstacles, namely the character of the parents and the teenagers in treating television literacy, the uneven distribution of media literacy socialization, the ineffective controlling function of KPID NTT, budget constraints, and broadcasting institutions. The solutions were NTT`s KPID collaborates with universities, schools, youth organizations, and creates critical media communities. The BP3A inserted relevant materials on media assistance and worked with the children's forum of Kupang City. AFB TV introduces the making process of television programs, and Kupang Christian Junior High School 1 invites NTT`s KPID to school.